The Influence Of Climate And Organizational Culture On Teacher Performance In Public Junior High Schools In Batu City - Novitasari, Eka Dian; Sobri, Ahmad Yusuf; Juharyanto, Juharyanto (PT. BATARI EDU CALYA, 2023)
The purpose of this study was to determine the organizational climate and organizational culture on teacher performance. This research uses a Quantitative approach. The research subjects were teachers at the State Junior High School in Batu City. Data collection in this study used a questionnaire with a Likert scale of 1-5. The population in this study were all teachers at the State Junior High School in Batu City. While the sample in this study amounted to 302 respondents using saturated samples. There are four tests in this study, namely descriptive analysis test, data validity and reliability test, prerequisite analysis test, and the last data hypothesis testing. Based on the results of the study, there is an organizational climate Path coefficient value of 0.119, meaning that the organizational climate has a direct influence on teacher performance. Then the organizational culture Path coefficient value of 0.436 means that the organizational climate directly contributes to the influence on teacher performance. Thus, it can be concluded that organizational climate and culture affect teacher performance. The better the climate and organizational culture in the Batu City State Junior High School, the more teacher performance will also increase.